2017
DOI: 10.1111/cdep.12224
|View full text |Cite
|
Sign up to set email alerts
|

Concern Over Internal, External, and Incidence Validity in Studies of Child‐Care Quantity and Externalizing Behavior Problems

Abstract: Literature reviews have concluded that extensive time in early child care is associated with frequent externalizing behavior problems in children. In this article, we address three domains of validity in the work underlying these conclusions: internal, external, and incidence validity. Regarding internal validity, most studies rely on covariate‐adjusted correlations, an approach that is especially vulnerable to selection bias. In studies using more rigorous approaches to reduce selection bias, results are mixe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 46 publications
3
29
1
1
Order By: Relevance
“…Also, relying on the richness of the assessments of the ALSPAC clinics, we were able to estimate PSW from an extensive set of child, parent, and socio-demographic characteristics. The use of the PSW control strategy is a more severe adjustment technique for taking account of social selection factors than covariate adjustment, as reported in previous childcare studies (Dearing & Zachrisson, 2017), increasing our confidence in the results observed in the present study.…”
Section: Strengths and Limitationssupporting
confidence: 81%
“…Also, relying on the richness of the assessments of the ALSPAC clinics, we were able to estimate PSW from an extensive set of child, parent, and socio-demographic characteristics. The use of the PSW control strategy is a more severe adjustment technique for taking account of social selection factors than covariate adjustment, as reported in previous childcare studies (Dearing & Zachrisson, 2017), increasing our confidence in the results observed in the present study.…”
Section: Strengths and Limitationssupporting
confidence: 81%
“…Conversely, Havnes and Mogstad (2011) found strong positive effects of time spent in kindergartens on Norwegian children’s later educational attainment. In sum, the evidence does not suggest a significant long term relationship between externalizing problems and hours spent in Norwegian high quality kindergartens (Dearing & Zachrisson, 2017; Dearing, Zachrisson & Nærde, 2015; Havnes & Mogstad, 2011; Zachrisson et al ., 2013).…”
Section: Parental Emotion‐related Socialization Behaviors (Ersbs)mentioning
confidence: 92%
“…It is unclear how universal access to early high quality child care effects externalizing child behavior problems in Norwegian preschoolers. Studies investigating the effects of child care have relied heavily on US samples, the results are mixed, and often inconsistent with the hypothesis that early non‐maternal care heightens the risk of externalizing disorders (Dearing & Zachrisson, 2017). In a sample of 75,271 1.5–3‐year‐old Norwegian children, Zachrisson, Dearing, Lekhal, and Toppelberg (2013) found little evidence that many hours spent in high quality child care caused externalizing problems in children.…”
Section: Parental Emotion‐related Socialization Behaviors (Ersbs)mentioning
confidence: 99%
“…One reason may be that paid parental leave policy makes 1 year the most common age of entry into ECEC in Norway, whereas many children in the United States enter some form of nonparental care by 9 months (Halle et al, 2009). More generally, however, the internal validity of many studies demonstrating negative consequences of ECEC has been called into question (Dearing & Zachrisson, 2017).…”
Section: Extending the Cumulative Knowledge About Ecec At Scale: Relementioning
confidence: 99%